DIMENSI KEMANUSIAAN DALAM ALQURAN DAN HADIS - Siregar, Idris (BASHA'IR: JURNAL STUDI AL-QUR'AN DAN TAFSIR, 2022)
The scholars agreed that the Quran is the primary source of Islamic law. On the one hand, the Quran's verses, particularly those dealing with the law, are extremely limited. Human deeds related to the law, on the other hand, continue to evolve. As a result, it is clear that there are human actions for which there is no explicit rule of law in the Quran. According to the author of this article, development steps are required because the Koran states that its presence is for human guidance in various aspects. In the form of a study of criteria in order to develop the deeds mentioned in the Koran. The author of this article attempts to explain and analyze the dimensions of humanity in the Koran in relation to human deeds using a lughawi approach and the principles of al-wadh'u, al-isti'm â l, and al-â mlu.